Al-Mawād at-Ta‘līmīyyah ‘alā Asās al-Kifāyah al-Ittiṣāliyyah fī al-Kitāb al-Madrasī “Al-‘Arabiyyah al-Mu‘āṣirah” li Eckehard Schulz - Furaida Ayu Musyrifa; Wildana Wargadinata; Nur Ila Ifawati; Khabibi Muhammad Luthfi (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darullughah Wadda'wah Pasuruan, 2021)
Abstract One of the textbooks used in different countries written by non-Arabs is